1985
DOI: 10.1159/000149646
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic (but not Nuclear) Hepatitis B Virus (HBV) Core Antigen Reflects HBV DNA Synthesis at the Level of the Infected Hepatocyte

Abstract: Hepatitis B virus (HBV) core antigen (HBcAg) detected by the peroxidase-antiperoxidase technique was present in the nucleus and cytoplasm of some infected hepatocytes but only in the cytoplasm of other hepatocytes. When cells expressing HBcAg were examined by in situ hybridization for the presence of HBV DNA, the intracellular level of cytoplasmic HBV replicative intermediate DNA correlated with the level of cytoplasmic HBcAg, but not with the presence or absence of nuclear HBcAg. This suggests that nuclear HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Considerable evidence exists that is consistent with this model. In humans (7,17), woodchucks (33), and, as illustrated here, chimpanzees (Fig. 8), a common feature of long-term infections is the emergence of large numbers of hepatocytes that no longer support hepadnavirus replication and antigen expression.…”
Section: Discussionmentioning
confidence: 92%
“…Considerable evidence exists that is consistent with this model. In humans (7,17), woodchucks (33), and, as illustrated here, chimpanzees (Fig. 8), a common feature of long-term infections is the emergence of large numbers of hepatocytes that no longer support hepadnavirus replication and antigen expression.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with predominantly nuclear HBcAg had higher levels of viral replication (8), whereas those with predominantly cytoplasmic HBcAg had significantly higher levels of biochemical and histological activities (9). However, some studies suggested that nuclear HBcAg might not be involved in HBV replication (1,11). In those studies, the majority of the patients had HBeAg-positive CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that cytoplasmic HBcAg was a more reliable marker of HBV replication than nuclear core HBcAg (1,11). Of the 35 intrahepatic-HBcAg-positive patients, 8 (22.9%) had a purely cytoplasmic distribution, 4 (11.4%) had a purely nuclear distribution, and 23 (65.7%) had a mixed cytoplasmic and nuclear distribution.…”
Section: Distribution Patterns Of Hbcag and Their Clinical And Patholmentioning
confidence: 99%
“…Typically, a large fraction of hepatocytes in the chronically HBV infected liver, including, but not limited to foci of altered hepatocytes (FAH) [20,21], do not contain detectable levels of virus antigens and nucleic acids [22][23][24][25][26][27][28][29][30][31][32], suggesting that these hepatocytes do not support HBV infection. Alternatively, some of these hepatocytes may express HBV surface antigen (HBsAg) in the absence of virus replication or expression of HBcAg.…”
Section: Introductionmentioning
confidence: 99%